Evaluating the effects of Climate Smart Agricultural (CSA) practices on productivity, adaptation, and mitigation indicators in Ethiopia: A meta-analysis approach - Adimassu, Zenebe; Tibebe, Degefie; Tamene, Lulseged; Abera, Wuletawu (Elsevier, 2025)
Climate-smart agricultural (CSA) practices have been adopted in various agroecological zones in Ethiopia to enhance productivity, improve resilience to climate change, and reduce greenhouse gas emissions through carbon sequestration. However, the overall impact of different CSA practices on productivity, adaptation, and mitigation metrics has not been exhaustively evaluated. The study employed a meta-analysis approach based on data from 220 peer-reviewed articles to assess the effects of commonly used CSA practices on these indicators across Ethiopia's diverse agroecological regions. The analysis identified over 20 CSA practices, with most—except soil bunds, level Fanya juu, and deficit irrigation—showing positive effects on productivity, peaking with drip irrigation (effect size of 2.15). Almost all practices also effectively reduced runoff and soil erosion, particularly crop residue mulching, which had a remarkable effect size of 2.95. Additionally, the findings indicated that various CSA practices enhanced soil organic matter and carbon stocks. Water management practices, especially drip and deficit irrigation, demonstrated significantly higher water productivity than traditional flood irrigation, with an effect size of up to 2.6. This water use efficiency suggests that these methods could free up substantial water resources for irrigating additional land, thus boosting crop production in water-scarce areas. However, the analysis revealed a negative effect size of up to −0.74 for income derived from drip irrigation, primarily due to the high costs of the necessary equipment. This highlights the need for reforms in duty and tax exemptions to improve farmers' profitability from drip irrigation systems. Overall, this meta-analysis assesses the impact of various CSA practices on key performance indicators productivity, adaptation, and mitigation—providing insights that can guide the packaging and implementation of the most effective CSA strategies across Ethiopia's agroecological zones.